2018
DOI: 10.1038/s41416-018-0124-8
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and risks of colorectal and small intestine cancer in Chinese adults: a prospective study of 0.5 million people

Abstract: BACKGROUND: Uncertainty remains about the associations of adiposity with intestinal cancer in China and by its anatomical subtype. METHODS: The prospective China Kadoorie Biobank recorded 3024 incident cases of colorectal (CRC) and 143 cases of small intestine (SIC) cancer during a 10-year follow-up among 509 568 participants without prior cancer at baseline. Cox regression was used to estimate adjusted hazard ratios (HRs) for specific cancers associated with adiposity. RESULTS: Overall mean body mass index (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In China, colorectal cancer (CRC) is one of the top five leading causes of cancer-associated death in men and women (7). A number of risk factors for CRC in Asia have been identified, including age, sex, family history and a high body fat percentage (8).…”
Section: Introductionmentioning
confidence: 99%
“…In China, colorectal cancer (CRC) is one of the top five leading causes of cancer-associated death in men and women (7). A number of risk factors for CRC in Asia have been identified, including age, sex, family history and a high body fat percentage (8).…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer has been found to be positively related to Western dietary habits and body mass index (BMI), as shown in studies that evaluated the complex epigenetic interactions among dietary intake, obesity and malignant colon tumor occurrence ( 40 ), and to be negatively related to physical activity, which is not related to the incidence of rectal cancer ( 13 , 41 ). Such alterations are likely to reflect lifestyle factors and dietary trends, including the enhanced intake of animal protein, especially red meat and/or processed meat, and high-sugar foods, the prevalence of sedentary lifestyles with decreased physical activity, and the consequent outcome of excess body weight ( 42 ). Furthermore, an epidemiological study of CRC in China between 1990 and 2009 showed that the increase in the detection rate of CRC in the proximal colorectum was higher than the increase in the detection rate of CRC located in the distal colon and rectum ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…That study, like ours, suggested a positive, albeit nonsignificant, association between BMI and carcinoid tumors only. Other prospective studies have been substantially smaller 13‐18 . The mechanistic pathways that would potentially link obesity to small intestine cancers, specifically among men and for carcinoid tumors, are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Other prospective studies have been substantially smaller. [13][14][15][16][17][18] The mechanistic pathways that would potentially link obesity to small intestine cancers, specifically among men and for carcinoid tumors, are unclear.…”
Section: Discussionmentioning
confidence: 99%